-6r-29=-5(2+5r)

Simple and best practice solution for -6r-29=-5(2+5r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6r-29=-5(2+5r) equation:


-6r-29=-5(2+5r)

We simplify the equation to the form, which is simple to understand
-6r-29=-5(2+5r)

Reorder the terms in parentheses
-6r-29=+(-10-25r)

Remove unnecessary parentheses
-6r-29=-10-25r

We move all terms containing r to the left and all other terms to the right.
-6r+25r=-10+29

We simplify left and right side of the equation.
+19r=+19

We divide both sides of the equation by 19 to get r.
r=1

See similar equations:

| 6y+1=-13 | | 11(x-6)=-11 | | r=(7+B)m | | 8x+2=5x-6 | | 11(x-6)=11 | | -4(1-4v)-v=-4-2v | | 5(x-6)=-10 | | -(3n-5)=-5n-7 | | lnx*sin^3*y*dx+x*cosy*dy=0 | | z^2+6z+20=0 | | 5a-5=6(-4a+4) | | (x-y)ydx-x^2dy=0 | | 16lw=v | | 2x^2-3xy-2y^2-2x-11y-12=0 | | 5-3x=14+2x | | 5x-3(x-5)+9(y-5)= | | x^4-9x+7=0 | | x^4-8x^3+9x^2+28x-60=0 | | -9+n=-2(-3-2n) | | 4m+9=7m+12 | | y^4+2y^2+1=0 | | 2(-5r-6)=-12-6r | | 8x+19=26 | | 4x+2=9-2x | | 4(5x+2)=-24+4x | | 3(k-3)-5=7k-(3k-2) | | f(x)=9xln(7x)-9x | | 2[3-4(5-7)]= | | -3(1r+3)=-1(-6+36) | | (6x+6)(2x^2+4x+4)= | | 9x-12=8x+3 | | -5a-25=5(-2a+4)-4a |

Equations solver categories